Diseño de un modelo de gestión ambiental con enfoque de economía circular para el sector pymes (2020)
This research defines an environmental management model from a product life cycle analysis based on the principles of the circular economy, determining the feasibility level of this system for the country's Mypimes. The aim of this approach is based on the low proportion of the number of companies of this type that adopt an environmental management model and the way in which they must rethink their processes to generate income, growth, and openness to new markets. This study proposes to overcome the negative concept given to the environmental issue which has been perceived as unnecessary. It can be achieved when cost reduction is evidenced by incorporating sustainability factors into the process through the principles of the circular economy.